Penyusunan Masterplan Desa Berbasis Mandiri-Wisata pada Desa Batulicin Irigasi, Kalimantan Selatan - Ira Mentayani; Bani Noor Muchamad; Muhammad Ibnu Saud; Naimatul Aufa (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
The village master plan is a document that can be a guide in determining the direction and development of a village. With all the potentials that exist, Batulicin Irigasi Village does not yet have a master plan that can be a guide and development scheme in managing village potentials and minimizing existing obstacles. Preparation of the Batulicin Irigasi Village master plan is a form of community service from the Faculty of Engineering ULM. This Village master plan aims to help residents in understanding the potential values of the village and directing its development in realizing the aspirations and expectations of the residents. The concept raised in the Batulicin Irigasi Village master plan is independent tourism village. The independent village concept is based on food independence, economic independence, energy independence, water independence, and disaster preparedness. The concept of a tourist village through the Batulicin Irigasi Village development strategy can be implemented in the form of plantation and livestock arrangement, street furniture signage, yard guidelines, UMKM product marketing, village water reserves, mixed-use building, criteria for supporting buildings, village branding, regional landscapes, and tourist packages. It is hoped that the final result of the Batulicin Irigasi Village master plan can bring great benefits to the development of the local area and the surrounding community.